Eksplorasi Faktor Penentu Perancangan Desain Penilaian Atribusi Kepengarangan Pada Teks Defamasi Anonim di Media Sosial Berbasis Stylo R Package - Rayhan, Muhammad; Boeriswati, Endry; Iskandar, Ifan (Jurnal Ilmiah Global Education, 2025)
This study aims to map the essential requirements for designing an authorship-attribution assessment instrument for anonymous defamatory texts on social media using stylometric analysis with the Stylo R Package. Employing a qualitative approach through in-depth interviews with purposive and random informants, the study explores how the public, law students, and forensic practitioners perceive the urgency of addressing anonymous defamation, the limitations of digital evidence, and the potential of linguistic analysis as an alternative evidentiary method. The data were examined using thematic analysis to identify functional, methodological, and ethical needs in applying stylometry. The findings reveal five core requirements: (1) urgent resolution of cases due to substantial social and psychological impacts; (2) safeguarding freedom of expression to prevent misclassification of legitimate criticism as defamation; (3) the need for alternative evidence when digital traces are incomplete; (4) scientific transparency through clear standards of validity, reliability, and replicability; and (5) regulatory frameworks, expert qualifications, and standardized procedures to avoid misuse. These findings provide a conceptual and empirical foundation for developing a credible, transparent, and contextually appropriate assessment instrument for authorship attribution in Indonesia’s digital forensic landscape.